REPRESENTATION OF SCHEMATIC VISUAL IN SOLVING PYTHAGORAS’ WORDPROBLEM - Suryaningrum, Christine Wulandari; Purwanto, Purwanto; Subanji, Subanji; Susanto, Hery (Universitas Negeri Malang, 2018)
The aim of this article is to identify the steps which were done by the students in solving Pythagoras? word problems. This study used qualitative research by using explorative descriptive approach. The subject of this study was four students who werein seventh grade of Junior High school of Muhammadiyah 1 Jember. The subjects givenone problem in the form of story that had to be done based on their styles. From the result analysis of the study was found that the students tried to understand the aim of the problems by using picture, compass direction, and Pythagoras? pattern. In solving Pythagoras? word problem, the students used representation of schematic visual. In making schematic picture, the students were supposedto be consistent with compass direction. The student that isconsistent with compass direction can make the schematic picture correctly and with a picture,the student can solve the word problems by using Pythagoras? pattern correctly. The student who is inconsistent with compass direction will get difficulties in making schematic picture and not be able to solve Pythagoras? word problems correctly.